2016
DOI: 10.1016/j.bbamcr.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-18 inhibits cell proliferation and motility mediated by inhibition of phosphorylation of PDK1 and Akt in human lung adenocarcinoma A549 cells

Abstract: Abnormal expression of claudin subtypes has been reported in various cancers. However, the pathological role of each claudin has not been clarified in detail. Claudin-18 was absent in human non-small cell and small cell lung cancers, although it is expressed in normal lung tissues. Here, we examined the effect of claudin-18 expression on the expression of junctional proteins, cell proliferation, and cell motility using human lung adenocarcinoma A549 cells. Real-time PCR and western blotting showed that exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…In the stomach, which was also enlarged, we observed expansion of the gastric mucosa (Supplemental Figure 4) with Figure 6E) indicates that the CLDN18.1 isoform is downregulated in LuAd. Consistent with these findings, overexpression of CLDN18.1 was found to suppress abnormal proliferation and motility of A549 cells, a human LuAd cell line, via inhibition of PI3K/PDK1/Akt signaling (75). Therapeutic targeting of CLDN18 should therefore take into account the specific isoform that is altered in a particular subtype of LuAd.…”
Section: Discussionsupporting
confidence: 54%
“…In the stomach, which was also enlarged, we observed expansion of the gastric mucosa (Supplemental Figure 4) with Figure 6E) indicates that the CLDN18.1 isoform is downregulated in LuAd. Consistent with these findings, overexpression of CLDN18.1 was found to suppress abnormal proliferation and motility of A549 cells, a human LuAd cell line, via inhibition of PI3K/PDK1/Akt signaling (75). Therapeutic targeting of CLDN18 should therefore take into account the specific isoform that is altered in a particular subtype of LuAd.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, studies in Cldn18 −/− mice showed that AKT phosphorylation is also regulated by CLDN18 in non-malignant cells from both embryonic lungs (Figure 4B) and adult AT2 cells (Supplemental Table 5), suggesting that the CLDN18.1/AKT axis is operative in normal cells and may therefore be involved in tumor initiation associated with loss of CLDN18. These results are consistent with inhibition of AKT recently observed in A549 LuAd cells upon CLDN18.1 expression (15). …”
Section: Discussionsupporting
confidence: 93%
“…CLDN18.1 is emerging as a tumor suppressor in lung alveolar epithelial cells (15,18). Compared to normal tissue, LuAd displays increased CLDN18.1 promoter methylation (Figure 1) and decreased mRNA expression (Figure 1 and Ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations